2011
DOI: 10.2528/pier11062007
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Synchronization Bandwidth of Rationally Synchronized Oscillators Based on Bifurcation Control

Abstract: Abstract-In this work, a nonlinear technique for the optimization of the synchronization bandwidth of Rationally Synchronized Oscillators (RSO) is presented. The circuit is forced to operate near a Hopf bifurcation point which is created around the frequency of the input reference signal. Under this operating regime, the reference signal is strongly amplified and the synchronization bandwidth of the circuit is considerably improved. A 5-3 GHz rationally synchronized oscillator has been optimized using the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…However, additional methods are required in order to improve the conversion gain of the circuit. In this work, the conversion gain will be enhanced through the application of a recently developed technique based on the independent control of the harmonic content of the autonomous signal and the working regime of the circuit [5][6][7].…”
Section: Conversion Gain Of the Hsommentioning
confidence: 99%
See 3 more Smart Citations
“…However, additional methods are required in order to improve the conversion gain of the circuit. In this work, the conversion gain will be enhanced through the application of a recently developed technique based on the independent control of the harmonic content of the autonomous signal and the working regime of the circuit [5][6][7].…”
Section: Conversion Gain Of the Hsommentioning
confidence: 99%
“…This phenomenon has been described as undesired in [24], since it causes noise amplification over some spectral bands. However, it has also been shown that, when is carefully controlled, this phenomenon can be exploited to strongly amplify a weak signal [5][6][7].…”
Section: Working Regime Close To a Hopf Bifurcation Pointmentioning
confidence: 99%
See 2 more Smart Citations
“…The noise characterization of oscillators is essential for the system engineers, because the device final performance is inherently defined by it [5][6][7]. At the same time, oscillator design presents high difficulties [8][9][10], although works by Randall and Hock [11] and Jackson [12], or even later works as González-Posadas et al and Jiménez-Martín et al [13,14] have tried to shed light on the conditions for proper oscillator design. These three last works have tried to unify all linear design methods by giving a global perspective, and they have characterized all oscillators as a feedback system using the Return Relations (RR) [15] and the Normalized Determinant Function (NDF) [16].…”
Section: Introductionmentioning
confidence: 99%